The development of variable system-based internet of things for the solar greenhouse and its application in lettuce - Li, Lingzhi; Han, Furong; Li, Jingjing; An, Shunwei; Shi, Kaili; Zhang, Shirui; Zhangzhong, Lili (Frontiers in Plant Science, 2024)
Horticulture is an important way to ensure food security amid the uncertainty of climate change because of its controllability. China has the largest area of horticultural facilities with a solar greenhouse acreage of more than 70 %. The east-west ridge orientation has recently become an important agronomic method to improve mechanization ; however, these ridge orientation changes shape differences between different ridges in crop water consumption, and the north-south ridge orientation is difficult to separate. Traditional irrigation makes it challenging to satisfy the crop water consumption requirements, and there is a lack of research on the regulation and adaptation of water consumption in the east-west ridge orientation; therefore, this study introduces a variable irrigation decision-making method based on the Internet of Things management and control system for an east-west ridge orientation. This system accumulates photosynthetic active radiation data to determine the irrigation time and water at different ridge crop canopies. The environmental online monitoring, central control, wireless valve control, ridge division irrigation execution, and irrigation monitoring modules were linked by a central controller to execute variable irrigation by ridge division. To replenish water on demand, and seting the variable irrigation decision-making (VRI) methods and traditional average irrigation decision-making (URI) methods in the system, and lettuce cultivation experiments were conducted to verify the effectiveness of the model and system. The results show that the difference of accumulated photosynthetically active radiation is the most significant between different ridges of the east-west ridge orientation, and the coefficient of variation is 43.77 %, which can be used as an activating factor for VRI methods. The irrigation water consumption, yield, water-use efficiencies, and irrigation water utilization of lettuce at different levels of irrigation were 307.12 L/m 2 , 5854.07 kg•ha -1 , 1391.47 kg•ha -1 •mm -1 , and 7.63 kg•cm -3 , respectively. Compared with the URI methods, the VRI method saved 10.02 % of water, increased yield by 9 %, and enhanced water use efficiency and irrigation water use efficiency by 12 % and 21.32 %, respectively. This study provides a new approach for improving crop production efficiency in the east-west ridge orientation.